Beyond material grievances: Analyzing the 2015 Bangladesh "No VAT on education" movement through a new social movement perspective - Ghosh, Saikot Chandra (Вестник Томского государственного университета. Философия. Социология. Политология)
The 2015 Bangladesh student protests against a proposed value-added tax (VAT) on private university tuition are conventionally framed in public imagery as a material struggle against an economic policy threatening educational access. This article reinterprets the movement through the New Social Movement (NSM) theoretical framework, which emphasises identity formation, post-material values, and cultural contestation over traditional economic redistribution. Drawing on the NSM theory, this analysis demonstrates how the protests transcended financial grievances to forge a collective student identity, resist the neoliberal commodification of education, and demand democratic participation within Bangladesh's increasingly authoritarian political context. Employing a qualitative framework, this study draws upon primary interview data and integrates them with an extensive corpus of secondary sources and historical analysis, framing the contemporary student movement as the broader continuum and evolution of Bangladesh's activist heritage. The findings reveal the "No VAT on Education" movement as a multifaceted critique of neoliberal governance, a reassertion of youth agency, and a symbolic challenge to systemic power, resonating with global NSM trends like Chile's 2011 education protests or South Africa's #FeesMustFall. This perspective challenges reductionist economic interpretations, offering a nuanced understanding of contemporary social movements in the Global South, where material and post-material struggles intersect. By bridging the immediate trigger of the VAT with broader societal aspirations - autonomy, justice, and cultural meaning - the 2015 movement reflects a transformative shift in Bangladesh's youth activism, suggesting enduring implications for the nation's political landscape and the applicability of the NSM theory in postcolonial, neoliberal settings.